2017
DOI: 10.1186/s12885-017-3219-3
|View full text |Cite
|
Sign up to set email alerts
|

Neural Wiskott-Aldrich syndrome protein (nWASP) is implicated in human lung cancer invasion

Abstract: Lung cancer is one of the most commonly diagnosed cancers with survival much lower in patients diagnosed with distal metastases. It is therefore imperative to identify pathways involved in lung cancer invasion and metastasis and to consider the therapeutic potential of agents that can interfere with these molecular pathways. This study examines nWASP expression in human lung cancer tissues and explores the effect of nWASP inhibition and knockdown on lung cancer cell behaviour.MethodsQPCR has been used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…High levels of N-WASP expression correlate with progression and/or poor outcome in human lung cancer (Frugtniet et al., 2017), PDAC (Guo et al., 2014), hepatocellular carcinoma (Jin et al., 2013), invasive breast ductal carcinoma (Yu et al., 2012), and esophageal squamous cell carcinoma (Wang et al., 2010). N-WASP was implicated in invasion and metastasis in a murine breast cancer model (Gligorijevic et al., 2012), but surprisingly, deletion of N-WASP in a murine model of colorectal cancer accelerated tumorigenesis (Morris et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of N-WASP expression correlate with progression and/or poor outcome in human lung cancer (Frugtniet et al., 2017), PDAC (Guo et al., 2014), hepatocellular carcinoma (Jin et al., 2013), invasive breast ductal carcinoma (Yu et al., 2012), and esophageal squamous cell carcinoma (Wang et al., 2010). N-WASP was implicated in invasion and metastasis in a murine breast cancer model (Gligorijevic et al., 2012), but surprisingly, deletion of N-WASP in a murine model of colorectal cancer accelerated tumorigenesis (Morris et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using a genetic model, we demonstrate that N-WASP function in keratinocytes is crucial for the formation of DMBA/TPAinduced skin tumors. Earlier, a role for N-WASP in cancer cell migration (18)(19)(20) and proliferation (20) was reported, but the mechanism underlying N-WASP-dependent growth regulation remained unclear. Our data suggest that N-WASP affects DMBA/ TPA-induced tumor formation by regulating cellular aging and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the significant rescue of speed and directionality observed with expression of Y104D-GMF γ in migrating c-Abl KD cells. Clinically, reports have demonstrated that GMF γ , N-WASP, and c-Abl are all upregulated in several pathologies afflicted by enhanced cell migration, suggesting this signaling cascade may play a role 9, 39, 55, 61-64.…”
Section: Discussionmentioning
confidence: 99%